2020
DOI: 10.1159/000509043
|View full text |Cite
|
Sign up to set email alerts
|

Pneumatic Lithotripsy versus Holmium Laser Lithotripsy in Percutaneous Nephrolithotomy for Patients with Guy’s Stone Score Grade IV Kidney Stone

Abstract: Background and Objective: The aim of this study was to compare the efficacy and reliability of holmium (Ho:YAG) laser lithotripsy (HLL) and pneumatic lithotripsy (PL) in percutaneous nephrolithotomy (PCNL) in the treatment of patients with Grade IV kidney stones based on Guy’s Stone Score. Study Design/Materials and Methods: This retrospective study included 103 patients with Grade IV kidney stones out of 440 patients who underwent PCNL through HLL and PL in Second Affiliated Hospital of Shantou University Med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
2
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 30 publications
2
2
2
Order By: Relevance
“…Most of previous study as 4 mm [18,25].The second SFR of s-PCNL+ULSand m-PCNL+hHL were comparable to previous study(second SFR were 82.1% and 84.2%). In the present study the number of tracts(1.35(s-PCNL+ULS), 1.20(m-PCNL+hHL)) were lesser then previous study [18,25], but we have comparable SFR because of exible ureteroscope-assisted PCNL was used in m-PCNL+hHL(47 patients) and s-PCNL+ULS(10 patients) in rist procedure. It may be di cult to see all kidney stones during single-tract percutaneous nephrolithotomy for staghorn kidney stones, there is a 20-50% probability that another percutaneous nephrolithotomy is needed, However, increasing the percutaneous renal channel will increase the risk of renal parenchymal injury.…”
Section: Resultssupporting
confidence: 82%
See 3 more Smart Citations
“…Most of previous study as 4 mm [18,25].The second SFR of s-PCNL+ULSand m-PCNL+hHL were comparable to previous study(second SFR were 82.1% and 84.2%). In the present study the number of tracts(1.35(s-PCNL+ULS), 1.20(m-PCNL+hHL)) were lesser then previous study [18,25], but we have comparable SFR because of exible ureteroscope-assisted PCNL was used in m-PCNL+hHL(47 patients) and s-PCNL+ULS(10 patients) in rist procedure. It may be di cult to see all kidney stones during single-tract percutaneous nephrolithotomy for staghorn kidney stones, there is a 20-50% probability that another percutaneous nephrolithotomy is needed, However, increasing the percutaneous renal channel will increase the risk of renal parenchymal injury.…”
Section: Resultssupporting
confidence: 82%
“…The rist SFR of complete staghorn for m-PCNL+hHL was lower then previous study by Hong YX et al [25] (59.09% Guy's Stone Score Grade IV) maybe attribute to the de nition of residual fragments, in the present study SFR was de ned as<3 mm. Most of previous study as 4 mm [18,25].The second SFR of s-PCNL+ULSand m-PCNL+hHL were comparable to previous study(second SFR were 82.1% and 84.2%).…”
Section: Resultscontrasting
confidence: 80%
See 2 more Smart Citations
“…29 Some studies have shown that multiple tract and ultrasonographic combined with fluoroscopic guidance can increase operation time, and the pneumatic lithotripsy and holmium laser lithotripsy had similar operation time. [30][31][32] In this study, we analyzed the correlation between puncture mode, tract number, lithotripsy method, and operation time and found that there was no correlation (Supplementary Table S1). Therefore, we have reason to believe that in this study, the higher multiple-tract rate, the higher combined guidance rate, and the higher holmium laser lithotripsy rate in the PSL-PCNL group do not affect the conclusion that the operation time in the PSL-PCNL group is shorter than that in the TP-PCNL group.…”
Section: Discussionmentioning
confidence: 99%